Megakaryocytic Characteristics in Diagnosis of Patients with Thrombocytopenia - Shahzad Ali Jiskani; Halar Rahim; Naila Noor; Rab Nawaz Sathio; Saba Ismaili Khawaja; Rizwan Ali Talpur (ziauddin University, 2024)
Background: The morphology of megakaryocytes plays a major role in thrombopoiesis. Dysmegakaryocytopoiesis and thrombocytopenia can result from imperfection in any phase of megakaryocytopoiesis. The structure, morphology, and characteristics of megakaryocytes can differentiate and identify the etiology of underlying diseases such as leukaemia, mixed anaemia, idiopathic, aplasia, or infiltration. This research aimed to comprehend megakaryocyte attributions and their contribution to the diagnosis of thrombocytopenia. Methods: This was a cross-sectional analysis of all successive cases of thrombocytopenia bone marrow aspirates over 12 months (January 2019 to December 2019) at the Department of Pathology, Indus Medical College Hospital Tando Muhammad Khan. With a 100X lens, megakaryocyte morphology was studied. Data were analysed by SPSS and Chi-square was performed to find correlation at the 95% confidence interval. Results: Among the 91 subjects of thrombocytopenia, the commonest etiology of thrombocytopenia was idiopathic thrombocytopenia 34(37.36%). The common morphological changes in megakaryocytes were hypolobated megakaryocytes and bare megakaryocyte nuclei. Megakaryocyte numbers were increased for 31 (91.17%) patients among idiopathic thrombocytopenia, though the megakaryocyte numbers were decreased among 19 (90.47%) patients having acute leukaemia. A change to immature, young, less polyploid and bare nuclei forms was observed in immune thrombocytopenia. Immature types were seen in 15 cases, 14 cases of bare megakaryocytic nuclei, 15 cases of hypolobation and one case of micromegakaryocytes. Conclusion: Many similarities among various haematological diseases were observed in megakaryocytic morphology. However, in megakaryocytic thrombocytopenia, high megakaryocyte counts and evidence of bare nuclei of megakaryocytes (p=0.02) and hypolobic types (p=0.03) proved important and play a very essential role in diagnosis. Keywords: Megakaryocytes; Thrombocytopenia; Bone Marrow Aspirate; Diagnosis; Dysmegakaryopoiesis.